Utility of a multigene testing for preoperative evaluation of indeterminate thyroid nodules: A prospective blinded single center study in China. (25th September 2020) - Song, Yuntao; Xu, Guohui; Ma, Tonghui; Zhu, Yanli; Yu, Hao; Yu, Wenbin; Wei, Wei; Wang, Tianxiao; Zhang, Bin
Abstract: Background: Thyroid nodules are highly prevalent, with fine‐needle aspiration (FNA) commonly used as the standard preoperative tool for their diagnosis. However, the method classifies some of the samples as indeterminate, leading to unnecessary surgery. In this study, we evaluated the value of next‐generation sequencing (NGS) for cancer diagnosis in indeterminate thyroid nodules. Materials and methods: We performed a prospective, blinded cohort study on 189 patients, with 196 Bethesda III/IV nodules. Specifically, we analyzed DNA mutations and RNA fusions across the FNA samples using NGS, then reviewed follow‐up reports from 84 nodules following definitive surgery, to determine the assay performance. Results: Enough DNA and RNA were obtained in 188 nodules, revealing mutations or fusions in 34.6% of them. The most frequently mutated genes were RAS, followed by BRAF V600E. Based on surgical pathology, 39% (33/84) and 4.8% (4/84) of the nodules were malignant and intermediate, respectively. According to the risk stratification criteria, 28 cases were categorized High‐Risk group, all of the resected nodules (n = 20) were malignant. Twenty‐four thyroid nodules were in the Low‐Risk group, 28.6% (4/14) surgically removed nodules were malignant. In the Benign‐Like category, 18.0% (9/50) were malignant. Five out of 13 nodules with benign mutations were resected, including SPOP, EZH1, and ZNF148, all of them were benign. If genetic alterations annotated with High‐Risk or Low‐Risk was considered as positive, and negative if Benign‐Like. Multigene testing revealed sensitivity, specificity, positive predictive values (PPV), and negative predictive value (NPV) of 73%, 80%, 71%, and 82%, respectively. In addition, if four intermediate nodules were counted as malignant, the PPV and NPV were 71% and 74%. Conclusion: Our results allow for further stratification of Bethesda III/IV thyroid nodules based on the risk of their malignancy. SPOP, EZH1, and ZNF148 mutations may be used as benign markers. Abstract : We introduced a multigene panal for cancer diagnosis in FNA‐indeterminate thyroid nodules, and evaluated its performance in Chinese population.